IMPLEMENTASI PEMBELAJARAN AQIDAH AKHLAK BERBASIS NILAI-NILAI ASWAJA PADA SISWA KELAS9VII DI MTS ALMAARIF 01 SINGOSARI - Rahmat Sudani; Dzulfikar Rodafi; Moh. Muslim (VICRATINA, 2022)
This research discusses the implementation of aqidah akhlaq learning based on aswaja values in grade VII students at Al Maarif Singosari Islamic Junior High School, Malang Regency. The purpose of this research is to determine the teacher’s planning in implementing aswaja values in aqidah akhlaq learning. The focus of the research used includes; how teacher’s plan in implementing aswaja values, how the application of aqidak akhlaq learning based on aswaja values and how the supporting factors, inhibiting, advantages and disadvantages of applying that. The data sources were provided by the aqidah akhlaq teachers, deputy head of curriculum and students. Data was collected through three methods: ) Interview, 2) Documentation, and 3) Observation. The results of this study indicate that, 1) The implementation of learning aqidah morals based on aswaja values comes from the Almaarif foundation module, 2013 curriculum, syllabus and learning implementation plans 2) The aswaja values including the values of: Tasamuh (tolerance), Tawazun (balance), Tawasuth (moderate), Ta’adul (fair) and amar ma'ruf nahi munkar.  3) supporting and inhibiting factors, a) socializing outside of school, b) poor communication with parents, c) lack of motivation and interest in learning. Strengths, habituation activities applied to students. Weaknesses, Students ability to accept teacher material.